THE UTILIZATION OF BRAND AWARENESS IN SOVIA KITCHEN'S BUSINESS TO INCREASE SALES - Muh. Alfikri; Syamsu Alam, Nur Halim (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to understand the utilization of brand awareness in the Sovia Kitchen business to increase sales. The research method used is qualitative descriptive research with data collection methods through observation, interviews, and documentation of a research object, which will then be analyzed using data analysis techniques, namely data reduction, data presentation, and conclusion drawing. Research results show that the utilization of brand awareness can be an important strategy for Sovia Kitchen in increasing sales. High brand awareness will make more consumers recognize and remember Sovia Kitchen, which in turn can influence their purchasing decisions. By building a strong brand image and increasing consumer awareness of the products and services offered, Sovia Kitchen can attract more new customers and retain existing ones, thereby directly contributing to increased sales. The strategies that may be implemented include the use of social media, consistent promotions, collaboration with influencers, and the improvement of product and service quality. All of this aims to enhance brand recognition and customer loyalty towards the Sovia Kitchen brand.